Tribology on the small scale : a modern textbook on friction, lubrication and wear - Mate, C. Mathew; Carpick, Robert W. (Oxford University Press, 2019)
Friction, lubrication, adhesion, and wear are prevalent physical phenomena in everyday life and in many key technologies. This text explains how these tribological phenomena originate from atomistic and microscale physical phenomena and shows how this understanding can be used to solve macroscale tribology problems.
This edition also issued in print: 2019.
Keywords: Tribology.; elektronické knihy; electronic books